Resources under regimes : technology, environment, and the state - Josephson, Paul R. (New histories of science, technology, and medicine., 2004)
Democratic or authoritarian, every society needs clean air and water; every state must manage its wildlife and natural resources. In this provocative, comparative study, Josephson asks to what extent the form of a government and its economy--centrally planned or market, colonial or post-colonial--determines how politicians, bureaucrats, scientists, engineers, and industrialists address environmental and social problems presented by the transformation of nature into a humanized landscape.